Implementation of Blended Learning Assisted by e-worksheets Focus on Enhancing Students Metacognitive Strategies - Sari, Fitriya Lukita Permata; Lengkana, Dewi; Meriza, Nadya (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This research aims to analyze the improvement of metacognitive strategies and students' self-directed learning in the implementation of blended learning assisted by E-LKPD Liveworksheets in 10th-grade classes at SMAN 2 Gedong Tataan during the second semester, focusing on environmental change topics. The research was conducted at SMAN 2 Gedong Tataan using a quasi-experimental method with a Pretest-Posttest Equivalent Control Groups Design. The research sample consisted of 64 students from 10th-grade Science 1 (X MIPA 1) and 10th-grade Science 2 (X MIPA 2) classes, selected through purposive sampling. Data were statistically analyzed using the Independent Samples T-test with a 5% confidence level, utilizing IBM SPSS Statistics 25. The research findings indicated that the implementation of blended learning assisted by E-LKPD Liveworksheets significantly improved students' metacognitive strategies, with a significance value of 0.000 (p < 0.05). The highest indicator for metacognitive strategies was procedural knowledge (75.78%) with a very good rating, while the lowest was debugging strategies (71.09%) with a good rating.Keywords: blended learning, E-LKPD, Liveworksheets, metacognitive strategies